The effect of audit fees, audit tenure, and auditor switching on audit report lag in financial sector companies listed on the BEI in 2021-2022 - Angelina Sijabat; Hisar Pangaribuan (International Journal of Applied Finance and Business Studies, 2023)
This study aims to prove whether audit fees, auditor tenure, and auditor switching can have a significant effect on audit report lag. This research uses quantitative methods with secondary data. The population of this study is financial sector companies published by the IDX in 2021- 2022. The number of samples used was 51 with a 2-year research period resulting in 102 sample data. The test results concluded that audit fees have a significant effect on audit report lag, while audit tenure and auditor switching do not have a significant effect on audit report lag. The suggestion from the researcher is that future researchers expand the research population so that the results obtained are more accurate.